Digital Transformation and Small Business Empowerment Among Muslim Women in Katsina Metropolis - Abubakar Isa Dutsin-Amare; Aminu Mukhtar; Nasir Musa Balarabe (Indonesian Journal for Islamic Studies, 2025)
This study explores the role of digital transformation in empowering small businesses owned by Muslim women in Katsina Metropolis. It addresses the challenges of limited access to digital tools and skills, which hinder the growth of women-led enterprises in the region. The research aims to evaluate how digital adoption enhances business performance, economic independence, and social empowerment. A mixed-method approach was employed, combining surveys and in-depth interviews with a sample of women entrepreneurs to gather insights into their experiences with digital platforms. Findings reveal that digital tools significantly improve market access by expanding the active customer base by 0.5% annually between 2018 and 2022 and enhancing revenue. Companies prioritizing exceptional digital experiences report customer satisfaction rates 1.6 times higher and average order values 1.9 times greater. It also reveals the expansion of customer engagement through which organizations with robust omnichannel experiences retain 89% of their customers, compared to 33% for those with weaker strategies and that businesses implementing personalized marketing strategies have achieved a 20-30% increase in customer engagement, and operational efficiency such as cost reduction by 20-30% through strategic digital transformation initiatives, productivity gain by which digital leaders witness a 55% increase in productivity compared to their peers and optimization process whereby, automation technologies have led businesses to experience a 25-40% reduction in operational costs. The study concludes that targeted interventions, including digital literacy programs and improved access to affordable technology, are critical for fostering inclusive growth and empowering Muslim women entrepreneurs in Katsina Metropolis.